Radiochemical Purity, at Expiry, and Radiochemical Stability of Iodine-131 Labelled Meta-iodobenzylguanidine Concentrates for Intravenous Infusion - Wafelman, Amon R.; Hoefnagel, Cornelis A.; Maes, Robert A. A.; Beijnen, Jos H. (Nuklearmedizin - NuclearMedicine, 1996)
Aim: The determination of the amount of free [131I]iodide in [13lI]meta-iodobenzylguanidine (1131I]MIBG) concentrates for intravenous infusion under different storage conditions derived from daily practice. Method: The percentage of free [131I]iodide was determined in [131I]MIBG concentrates (1.6-3.9 GBq in 7.5 ml), kept on dry ice (up to expiry, 3 days after production) or, after thawing, at room temperature (up to 24 h). A validated solid phase extraction (SPE) assay was used. Results: Free [131 Niodide increased from 1.9% ± 0.34% at production to 4.4% ± 0.67% (mean ± SD; n = 5) at expiry in 3.7 GBq per 7.5 ml [131I]MIBG infusion concentrates, stored on dry ice (-78° C). At room temperature, formation of free [131 Niodide was found to be dependent on the radioactive concentration of the fluid. [131I]iodide levels increased from 3.1%, immediately after thawing, to 6.6% and 16.6% at t = 5 and 24 h, respectively, for a 3.9 GBq per 7.5 ml concentrate. Conclusion: The investigated formulation of [131I]MIBG concentrates, stored in its original packing containing dry ice, can generally be used up to expiry. After thawing, the undiluted concentrates should be administered to a patient within 3.5 h.
Keywords: Infusion concentrates; [131I]iodide; [131I]MIBG; Radiochemical purity; radiochemical stability